Evaluation of Psychometric Properties of Voice Activity and Participation Profile (VAPP): A Spanish Version - Bermúdez De Alvear, Rosa; Gálvez Ruiz, Pablo; Martínez Arquero, Ginés; Rando-Márquez, Sara; Fernández-Contreras, Elena (Journal of Voice, 2018)
Objectives This study aimed to analyze the psychometric properties of the Spanish version of the Voice Activity and Participation Profile (SVAPP) questionnaire. Study design A randomized, cross-sectional sampling strategy with controls was used. Methods Two samples with a total of 169 participants were analyzed, specifically 61 men (mean age 37.02) and 108 women (mean age 37.78). Of these participants, 112 were patients and 57 were controls. The instrument was submitted to reliability (internal consistency and corrected item-total correlations) and reproducibility analyses. Validation assessment was based on the construct validity, convergent validity, discriminant validity, and concurrent validity. Results The global internal consistency was excellent (Cronbach's α = 0.976), corrected item-total correlations were satisfactory and ranged 0.63–0.89, and factor loadings were above 0.50. The different subscales showed good internal consistency (alpha coefficients ranged 0.830–0.956) and test-retest values were consistently associated. The exploratory factor analysis evidenced a strongly defined five factors internal structure, with factors loadings ranging 0.51–0.86. Convergent validity demonstrated that all subscales and scores were very strongly correlated (Pearson r above 0.735) and significantly associated. The discriminant validity analysis showed that SVAPP had good specificity to distinguish dysphonic from healthy voice subjects. Concurrent validity with Voice Handicap Index Spanish version (SVHI) showed very strong correlations between total scores, and between SVHI total score and SVAPP Daily and Social Communication subscales; correlations between both tests subscales were strong; only between SVAPP Work and SVHI Physical sections correlations were moderate. Conclusions The findings of the present study demonstrated evidence for the SVAPP questionnaire reliability and validity, and provided insightful implications of voice disorders on Spanish patients' quality of life. However, further investigations are required.
Keywords: voice; quality of life; activity limitation; participation restriction; reliability; Scopus; JCR